ODONTOGENIC INFECTIONS MICROBIOLOGY AND MANAGEMENT - Shah, Dr Rishabh; Khare, Dr Vikram V; Dayanithi; Dayanithi; Gulia, Dr. Sunil Kumar; Pate, Sumaiyyal; Khemka, Aakriti (International Journal of Psychosocial Rehabilitation, 2020)
Epidemiological triad of infection consists of a susceptible host, microbial organism and environment .Oral cavity encompasses a wide variety of microbial organism in which many of them possess virulent properties. Infection of oral and maxillofacial region are mostly odontogenic in origin. Infections occur because of the disturbance in the normal bacterial flora or from an external agent. Early recognition and management of these infections are essential to reduce the further complications. This article reviews the microbiology and management of odontogenic infections.